2017
DOI: 10.1177/2325967117723608
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Tissue Quality of Cartilage Flaps From Patients With Femoroacetabular Hip Impingement: A Matched-Control Comparison

Abstract: Background:Chondrolabral damage is commonly observed in patients with cam-type femoroacetabular impingement (FAI). Chondral flap reattachment has recently been proposed as a possible preservation technique.Purpose/Hypothesis:The purpose of this study was to determine the viability and tissue quality of chondral flaps from patients with FAI at the time of arthroscopy. It was hypothesized that chondral flaps from patients with cam lesions of the hip would exhibit less viability and greater tissue degeneration th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 66 publications
(98 reference statements)
0
12
0
1
Order By: Relevance
“…Microscopic degenerative OA changes in head-neck and acetabular cartilage have been reported previously. 18,23,28,33,37 The current study is distinct and among the first published because it includes cartilage from the head-neck and acetabulum as well as the synovium from patients with early-stage FAI, patients with late-stage OA secondary to FAI, and healthy controls. Moreover, all samples were characterized with H&E staining, safranin-O staining, and immunostaining for inflammation-related markers.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic degenerative OA changes in head-neck and acetabular cartilage have been reported previously. 18,23,28,33,37 The current study is distinct and among the first published because it includes cartilage from the head-neck and acetabulum as well as the synovium from patients with early-stage FAI, patients with late-stage OA secondary to FAI, and healthy controls. Moreover, all samples were characterized with H&E staining, safranin-O staining, and immunostaining for inflammation-related markers.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that acetabular chondral flaps may occur in patients with FAI, 10,24,28,31,38 the literature on chondral flaps in patients with hip dysplasia is sparse. 30 Furthermore, no prior studies have systematically characterized the morphology of these chondral flaps as outside-in versus inside-out based on the underlying radiographic diagnosis.…”
mentioning
confidence: 99%
“…The presence of these markers is important, as it indicates that the cells maintained chondrogenic features after harvest. There is a known negative association between collagen II staining and increasing Osteoarthritis Research Society International grade, as documented by Rodriguez-Fontan et al 23 : specifically, the higher the Osteoarthritis Research Society International grade, the more advanced the degeneration. 31 Histologic review performed by Rodriguez-Fontan et al revealed a loss of normal cartilage architecture associated with increased degeneration, as seen with the loss of columnar chondrocyte orientation, surface integrity, and extracellular matrix and collagen type II formation.…”
Section: Discussionmentioning
confidence: 88%
“…31 Histologic review performed by Rodriguez-Fontan et al revealed a loss of normal cartilage architecture associated with increased degeneration, as seen with the loss of columnar chondrocyte orientation, surface integrity, and extracellular matrix and collagen type II formation. 23 The presence of native cartilage markers in femoral cartilage after harvest is encouraging in that it can maintain chondrogenic capabilities despite the mechanical effect of FAI morphology.…”
Section: Discussionmentioning
confidence: 99%